Intraoral electrostimulator for xerostomia relief: A long-term, multicenter, open-label, uncontrolled, clinical trial - MUMCU, GONCA (Mosby Inc., 2012)
Objective. A previous sham-controlled multinational study demonstrated the short-term efficacy and safety for xerostomia treatment of an intraoral device that delivers electrostimulation to the lingual nerve. The objective of this study was to test the hypothesis that those beneficial effects would be sustained over an 11-month period. Study Design. The device was tested on a mixed sample of 94 patients with xerostomia in an open-label, uncontrolled, prospective multicenter trial. Statutory outcome assessments were done at 5th, 8th, and 11th months and analyzed by multiple comparisons. Results. Improvements achieved at month 5 from baseline were sustained throughout the follow-up period for the primary outcome, xerostomia severity, and the secondary outcomes resting whole salivary flow rate, xerostomia frequency, oral discomfort, and difficulties in speech, swallowing, and sleeping. No significant side effects were detected. Conclusions. The beneficial effects of a removable intraoral electrostimulating device were sustained for an 11-month period. © 2012 Elsevier Inc. All rights reserved.